PENTINGNYA RISET KEBIJAKAN DALAM PEMBUATAN KEBIJAKAN PUBLIK UNGGUL DI INDONESIA - Anugerah Yuka Asmara (Department of Public Administration, Universitas Negeri Surabaya, 2017)
A public policy in Indonesia tends to be implemented insufficiently good, although a public policy making process has been undertaken sequentially. One of factors is the neglected research results, particularly a social or policy research has not become yet as a main consideration for the policy makers. They tend using an intuition consideration and a personal experience rather than using the research results in determining a new public policy. Unfortunately, majority of policy makers use a political and economic consideration in each of stages of policy making process to fulfill the various elite interests, not for public as a whole. Important to be known that a evidence-based policy can create a sound public policy. It is a policy to resolve the recent problems, to minimize the mistakes/failures, and giving a bright wish for people in the future. The aim of this sound public policy is to hoist the image and trust of Indonesian Government in the perspective of Indonesian and foreign people currently.